Social Excursions During the In-between Spaces of Lessons. Students' Smartphone Use in the Upper Secondary School Classroom. Issue 4 (7th June 2021) - Olin-Scheller, Christina; Tanner, Marie; Asplund, Stig-Börje; Kontio, Janne; Wikström, Peter
ABSTRACT: In this article, we focus on smartphone use initiated by students during lessons, with the aim of deepening the knowledge of when and why this use happens. Our methodological approach is video-ethnographic. The empirical data consists of 20 focus students in 9 upper secondary school classes, comprising 70 h of video material. The results show that the use of smartphones most often occurs in what we call the in-between spaces during lessons. These spaces are individual and negotiated within the classroom interaction frames. We argue that turning to one's phone during an in-between space may largely be seen as a social excursion that is generally smoothly and tactfully integrated into the social order of the classroom.